Telework by region and the impact of COVID-19 pandemic: An occupational analysis - Matteo Sostero; Martina Bisello; Enrique Fernández-Macías (European Commission, Joint Research Centre (JRC), 2024)
Following the sudden expansion of telework across the EU during the COVID-19 pandemic, this study reveals a widespread increase in the prevalence of work from home across EU countries, regions, and territorial typologies. While telework rates have slightly receded from their peak at the height of COVID-19 restrictions, they remain markedly higher than pre-pandemic levels nearly everywhere in the EU, reflecting a lasting shift in work practices. Despite this common trend, stark disparities persist, especially between urban and rural areas, between capital regions and the rest, but also across countries. Regional analysis of the EU Labour Force Survey underscores the critical role of regional occupational structures in explaining differences in the local prevalence of telework. The findings show that technical teleworkability, as determined by occupational tasks, has become an even more significant predictor of the regional prevalence of telework after the pandemic. The study also challenges some common assumptions about rural internet connectivity, which has improved remarkably since before the pandemic, and which may now matter relatively less than regional occupational structure as a driver of telework. Our research also suggests that both the extent and frequency of telework matter for regional development, highlighting the nuanced policy trade-offs to promoting telework for sustainability and regional equity in a post-pandemic landscape.
Keywords: 330; Telework; occupations; division of labour; regional employment